Psychological distress in women and men living with HIV in Spain: a cross-sectional telephone survey. Issue 3 (14th July 2020) - Garriga, Cesar; Gutiérrez Trujillo, Lourdes; Del Romero, Jorge; Montero, Marta; Pérez-Elías, María Jesús; Culqui Lévano, Dante; Gutierrez, Félix; Gómez-Sirvent, Juan Luis; Peña-Monje, Alejandro; Blanco, José Ramón; Rodríguez-Arenas, María Angeles
Abstract : Background: Psychological distress includes a broader range of experiences, varying from less severe symptoms of depression and anxiety to severe psychiatric disease. Global estimates for depression and anxiety in 2017 were 3.4% and 3.8%, respectively. While for people living with HIV, global estimates were 16% and 33%, respectively. Objective: We aimed to determine the prevalence of psychological distress by gender and associated characteristics in patients living with HIV. Methods: A cross-sectional study was conducted within the Spanish HIV Research Network CoRIS. Participants were interviewed by telephone between 2010 and 2014 about their psychological distress, sociodemographics, drug consumption, self-perceived health and combined antiretroviral therapy (cART) adherence. Laboratory tests and medical history details were collected from CoRIS. Logistic regression was used to identify characteristics associated with psychological distress. Findings: We interviewed 99 women and 464 men, both living with HIV. A greater proportion of women (51, 51.5%) reported psychological distress than men (179, 38.6%; p<0.01). Non-adherence to cART (OR 4.6 and 2.3, 95% CI 1.4‒15.1 and 1.3‒4.2) and non-use of cART (8.4 and 1.8, 2.2‒32.4 and 1.1‒2.8) were related to psychological distress in women and men, respectively. Spending little time in leisure-based physical activity was related to psychological distress in women (3.1, 1.1‒9.0). Living alone (2.0, 1.3‒3.0) and being unemployed (2.3, 1.4‒3.6) were related to psychological distress in men. Conclusions and clinical implications: As people living with HIV have a high prevalence of psychological distress, their regular screening appointments should include psychological assessment. A gendered approach is needed to detect and manage psychological distress.